Distribution of human papillomavirus (HPV) genotypes and bacterial vaginosis presence in cervical samples from Paraguayan indigenous - Mongelos, Pamela (2015)
Fil: Mongelos, Pamela. National University of Asuncion. Health Sciences Research Institute. Department of Public Health; Paraguay.